2002
DOI: 10.1136/gut.51.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Is anorectal endosonography valuable in dyschesia?

Abstract: Aims: Dyschesia can be provoked by inappropriate defecation movements. The aim of this prospective study was to demonstrate dysfunction of the anal sphincter and/or the musculus (m.) puborectalis in patients with dyschesia using anorectal endosonography. Methods: Twenty consecutive patients with a medical history of dyschesia and a control group of 20 healthy subjects underwent linear anorectal endosonography (Toshiba models IUV 5060 and PVL-625 RT). In both groups, the dimensions of the anal sphincter and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
1
28
0
2
Order By: Relevance
“…The preliminary results of the present study indicate that any radiological evidence of paradoxical contraction of the pelvic-floor muscle and acute angulation of the anorectal angle during straining identified by dynamic MRI in the supine position would suffice to differentiate normal from abnormal defecation dynamics. It is noteworthy that ARM and anorectal endosonography also require the patient to adopt a leftlateral position (1,18,22).…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary results of the present study indicate that any radiological evidence of paradoxical contraction of the pelvic-floor muscle and acute angulation of the anorectal angle during straining identified by dynamic MRI in the supine position would suffice to differentiate normal from abnormal defecation dynamics. It is noteworthy that ARM and anorectal endosonography also require the patient to adopt a leftlateral position (1,18,22).…”
Section: Discussionmentioning
confidence: 99%
“…In an assessment of patients with anismus, Van Outryve et al (29) used linear transrectal sonography to measure muscle length and thickness at rest and during straining and found statistically significant differences. Brusciano et al (7) used 2-D endosonography to identify anismus in patients with obstructed defecation and concluded that during straining differences of less than 0.5 cm between the internal border of the PR and the transducer are suggestive of anismus.…”
Section: Discussionmentioning
confidence: 99%
“…Once identified and quantified, anatomical and functional changes can be correlated with clinical symptoms and proctological findings (6) . Defecography, manometry, electromyography and, more recently, dynamic magnetic resonance scanning and dynamic anorectal ultrasonography, have all been used to diagnose patients with pelvic floor dysfunctions (1,2,3,4,5,6,7,8,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30) . Advances in ultrasound technology includes the development of the three-dimensional (3D) anorectal transducer and allows to clearly visualize the anatomic configuration of the anal canal in multiplane images (27) but the twodimensional (2D) ultrasound can be useful in the diagnosis of anorectal disease (7,10,24) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tem sido demonstrada a aplicação da ultrasonografia dinâmica [9][10][11][12] e a ressonância nuclear magnética dinâmica [13][14][15] na avaliação da Síndrome da Defecação Obstruída (SDO), com resultados bastante satisfatórios. As técnicas desenvolvidas com a ultrasonografia dinâmica utilizam tipos diferentes de transdutores.…”
Section: Introductionunclassified